Impact of flow variability and sediment characteristics on channel width evolution in laboratory streams. Issue 1 (2nd January 2019) - Vargas-Luna, Andrés; Crosato, Alessandra; Byishimo, Protogene; Uijttewaal, Wim S. J.
ABSTRACT: Alluvial rivers are shaped by sequences of water flows excavating their channels. Observations show that besides the magnitude, the frequency and duration of streamflow oscillations might also be important for the river channel formation. In addition, the river morphology appears influenced by both size and degree of uniformity of the sediment. Nevertheless, many morphodynamic studies still represent the flow regime with a single value of the discharge, often corresponding to the bankfull condition, and the sediment with its median grain size. This work investigates the effects of streamflow variability and sediment characteristics on channel width formation, analysing the evolution of experimental streams with different sediments and discharge hydrographs. Results show that the formative condition of the channel width is not the geometric bankfull flow but a rather frequent peak flow. Remarkably different channel configurations arise from different sediment characteristics in the laboratory, where sediment non-uniformity produces more stable banks.